The impact of physical therapy direct access policy on opioid shipments and opioid-related deaths: A difference-in-differences analysis - Geronimo Bejarano; Peter Hull; James J. Young; David J. Meyers; Kevin N. Griffith (PLoS ONE, 2026)
Background We exploit state-level policy changes for physical therapy direct access to estimate the effect of enacting direct access physical therapy policy on per-capita opioid pill volume (PCPV) and opioid-related deaths (ORD) compared to states without direct access to physical therapy. Methods We used a staggered difference-in-differences analysis to assess changes in PCPV and ORD for states that did (treatment states) and did not enact (control states) direct access physical therapy policies between 2006–2014. Various sensitivity analyses including synthetic control methods were used to check the robustness of our results. Results Treatment states had higher baseline PCPV (29.9 vs. 27.3) and ORD (27.2 vs. 16.9) compared to the control states. Pre-trends in PCPV and ORD were parallel between treatment and control states. After direct access physical therapy policies were enacted, PCPV was significantly reduced by −4.6 (95% confidence interval: −6.2 to −3.0) percentage points, a 15.4% relative reduction. There was no significant difference in ORDs (−2.3 [95% confidence interval: −7.2 to 2.6]). Conclusion Direct access physical therapy policies significantly reduced PCPV but not ORDs. Our results suggest that administrative barriers to physical therapy may lead to greater opioid reliance and reduced population health.